Space-time spectra of Northern Hemispheric Rossby waves at tropospheric and stratospheric levels during extended winter - Riboldi, Jacopo; Schutte, Michael (Uppsala University, 2025)
Data contains daily Rossby wave spectra that were obtained from a double Fourier transform, in space and time, and displayed in harmonics with wavenumber n and phase speed c. The underlying dataset for the space-time Fourier analysis is meridional wind of ERA5.

For further details about data, see section 2.3 in Schutte et al., 2024 (https://doi.org/10.5194/wcd-5-733-2024).

Data is split into two files:
1. allyears_NDJFMA_35_75_spectra_v_61d_strato.nc - spectra averaged between 35◦N-75◦N for the stratosphere (10, 50, 100 and 200 hPa) and,
2. allyears_NDJFMA_35_75_spectra_v_61d_tropo.nc - spectra averaged between 35◦N-75◦N in the troposphere (250, 400, 500, 600, 700 and 850 hPa).

The files contain data for November to April (NDJFMA) for years 1979 to 2021.

[Detta är en maskinöversättning. Se den engelska sidan för den ursprungliga beskrivningen]

Data innehåller dagliga Rossbyvågspektra som erhållits från en dubbel Fouriers transform, i rum och tid, och visas i harmonier med vågnummer n och fassnabbhet c. Den underliggande datamängden för rum-tid-Fourieranalysen är ERA5:s meridionala vind.

För ytterligare detaljer om datan, se avsnitt 2.3 i Schutte et al., 2024 (https://doi.org/10.5194/wcd-5-733-2024).

Datan är uppdelad i två filer:
1. allyears_NDJFMA_35_75_spectra_v_61d_strato.nc - spektra genomsnittliga mellan 35°N-75°N för stratosfären (10, 50, 100 and 200 hPa) och,
2. allyears_NDJFMA_35_75_spectra_v_61d_tropo.nc - spektra genomsnittliga mellan 35°N-75°N i troposfären (250, 400, 500, 600, 700 and 850 hPa).

Filerna innehåller data för november till april (NDJFMA) för åren 1979 till 2021.
Space-time spectra of Northern Hemispheric Rossby waves at tropospheric and stratospheric levels during extended winter
Keywords: WAVE SPECTRA; Meteorological geographical features; Geografiska meteorologiska förhållanden; rossby waves; stratosphere; troposphere; Climate Science; Klimatvetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi